2013
DOI: 10.1007/s00414-013-0863-2
|View full text |Cite
|
Sign up to set email alerts
|

Age determination of adult individuals by three-dimensional modelling of canines

Abstract: Accurate age determination is fundamental in both forensic medicine and anthropology. Many methods that relate dental characteristics to adult age have been proposed, but there is still no simple and reliable method that does not damage the study material. The aim of this work was to propose a relevant and practical technique for determining age in adults that could be used in both living and deceased individuals. The sample was composed of 210 CT scans from individuals aged from 15 to 85 years old, with four … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
24
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 50 publications
6
24
1
Order By: Relevance
“…Furthermore, the results of the present study showed that such a correlation was stronger in males compared to females, i.e. the pulp-to-tooth volume ratio is a more favorable variable in males compared to females to estimate age, indicating that gender affects the formula used to estimate age, consistent with the results reported by Tardivo et al (14) in relation to canines. However, in a study by Star et al (13), the correlation was stronger in females compared to males.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Furthermore, the results of the present study showed that such a correlation was stronger in males compared to females, i.e. the pulp-to-tooth volume ratio is a more favorable variable in males compared to females to estimate age, indicating that gender affects the formula used to estimate age, consistent with the results reported by Tardivo et al (14) in relation to canines. However, in a study by Star et al (13), the correlation was stronger in females compared to males.…”
Section: Discussionsupporting
confidence: 92%
“…However, a study in which only mandibular central incisors were used, the results were less valid (12). Tardivo et al (14) reported that simultaneous use of two maxi-llary canines are better and stronger in estimating age compared to the use of four human canine teeth, indicating the higher capacity of maxillary canines, compared to mandibular canines, for estimating age that consistent with the results of the present study. These conclusions might be attributed to the larger size and less anatomic variations of these teeth.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…M. Grassberger et al [12] regards the CT images and 3D reconstruction as the useful tool in clinical forensic casework. In short, the application of medical imaging data and direct 3D reconstructions are becoming more and more recognized by forensic experts [2,4,5,[10][11][12][13][14][15][16][17].…”
Section: Discussionmentioning
confidence: 99%